Crusader Military Order Fortifications along the Carmel Coast - Lantos, Sara; Gambash, Gil; Yasur-Landau, Assaf; Khamisy, Rabei G. (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)
The Carmel Coast has historically functioned as a vital highway, and it did so during the Frankish period. This study focuses on the 12th‒13th century castles along this coastal route, owned by the Military Orders, which played a pivotal role in the micro-region. We compare three of these strongholds using data from prior excavations and newly conducted surveys, including innovative aerial surveys that have generated unprecedented orthophotos and models of two of the sites. Our findings illuminate the architectural strategies employed by the Military Orders and enhance our understanding of the dynamics of this coastal micro-region during the Frankish period.